Problematika Lafal dalam Kajian Bahasa - Methia Farina (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
Problems of pronunciation and meaning are very numerous in contemporary linguistic studies which have been studied for their history since the time of the classical Arabs. The problem of pronunciation and meaning in terms of art and technique has been tried to be analyzed. The same sentence can have different meanings due to differences in pronunciation intonation, context, situations and conditions of speech. A word continues to develop according to the development of human thought and needs and gives rise to new meanings. The problem of dilalah can be seen in terms of musytarak, taddad and taraduf.